2020
DOI: 10.1080/10528008.2020.1837633
|View full text |Cite
|
Sign up to set email alerts
|

Future Thinking Continuity of Learning in Marketing: A Student Perspective on Crisis Management in Higher Education

Abstract: To boost understanding of how universities can develop strategies to ensure continuity of learning in anticipation of future crises, this research asked business students to reflect on their university's response to the COVID-19 pandemic and to discuss their preferred future of higher education in times of crisis. First, students were asked what their university and professors did well and what they did poorly as the COVID-19 pandemic unfolded. Second, participants were asked to discuss factors that facilitate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 36 publications
0
26
0
Order By: Relevance
“…This topic is of utmost importance to marketing educators because marketing professors are frontline service providers who must understand students’ changing needs to motivate learning (Vander Schee, 2010). Furthermore, demonstrating effective marketing and selling techniques is important to marketing professors who are in a unique position to demonstrate what they teach (Rayburn et al, 2020). Additionally, while this research topic applies to other disciplines dealing with the pandemic, marketing faculty are more skilled at communication.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This topic is of utmost importance to marketing educators because marketing professors are frontline service providers who must understand students’ changing needs to motivate learning (Vander Schee, 2010). Furthermore, demonstrating effective marketing and selling techniques is important to marketing professors who are in a unique position to demonstrate what they teach (Rayburn et al, 2020). Additionally, while this research topic applies to other disciplines dealing with the pandemic, marketing faculty are more skilled at communication.…”
mentioning
confidence: 99%
“…Additionally, while this research topic applies to other disciplines dealing with the pandemic, marketing faculty are more skilled at communication. They, therefore, are in a distinct situation to communicate pandemic pedagogy solutions across departments and campuses (Rayburn et al, 2020).…”
mentioning
confidence: 99%
“…In the past, crisis events in global higher education institutions (HEIs) have primarily centred on issues concerning harassment, bullying and discrimination suits, administrative scandals, student unrest, strikes, mass shootings, suicides, severe weather events, and terrorist attacks (Wang & Hutchins, 2010;Studenberg, 2017). Crisis management plans in this regard have focused mostly on human and environmental safety as part of the HEI goals (Rayburn, Anderson & Sierra, 2020). By caring for and ensuring a safe environment for all members of the campus community during a crisis, students can readily transition to safer conditions that enable the continuity of their academic experience.…”
Section: Introductionmentioning
confidence: 99%
“…The current Covid-19 pandemic has revealed the need for institutions to have adequate short-and long-term crisis management plans to ensure that the educational process is uninterrupted and to maintain learning continuity (Rayburn et al, 2020). A recent World Bank Education (2020) report on tertiary institutions' responses to the Covid-19 crisis reveals widespread institutional disruptions including those related to mass student displacements, weakened vital campus services and support, increased inequity, and inequality in accessing education.…”
Section: Introductionmentioning
confidence: 99%
“…There are lessons to learn from this for all students and this study gives a unique perspective to teachers about issues students are coping with during the pandemic. Rayburn et al (2020) empirically examined data from marketing students and revealed a student perspective on crisis management in higher education. They mentioned that universities, professors, and students achieve shared responsibility for the continuity of learning.…”
Section: Introductionmentioning
confidence: 99%